THE IMPLEMENTATION OF NEOCLASSICAL MANAGEMENT IN LEARNING TAHFIDZ QUR'AN AT KENDAL STATE ALIYAH MADRASAH AND SALATIGA STATE ALIYAH MADRASAH - Almira Wahyu Aulia; Muhammad Ulfi Fadli (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to analyze neoclassical Qur'an tahfid program management implementation in MAN Kendal and MAN Salatiga. This research is an inductive approach. This research was collected by observation, interview, and documentation techniques. Data analysis techniques used in this research are data collection, reduction, presentation, conclusion drawing, and leveraging. The results of this study indicate that the implementation of neoclassical management in the tahfid Qur'an program at MAN Kendal by using the method of motivation and good cooperation is a characteristic of neoclassical (human relations) to improve the tahfid program. In contrast, the implementation of neoclassical tahfidzul Qur'an program management at MAN Salatiga is the cooperation between the Head of Madrasah employees or members of the organization to achieve the planned goals. As well as encouragement and motivation from fellow teachers, students to improve the tahfid program. Includes a systematic description of planning, organizing, directing, and evaluating.